Hubungan Asupan Kalsium Dan Aktivitas Fisik Terhadap Profil Lipid Pada Penderita Jantung Koroner Rawat Jalan di RSUP Sanglah Denpasar - Gusti Ayu Putu Chandra Devi; Pande Putu Sri Sugiani; Ni Komang Wiardani (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2019)
This study aimed at knowing the correlation between calcium intake and physical activity on lipid profile in patients with coronary heart outpatient at Sanglah Hospital Denpasar. The research design that was used in this research was analytical research with a cross-sectional approach. The number of samples was 48 people used the Spearman correlation test. The Characteristic of the sample was the number of male samples as much as 42 people and women 6 people. The largest number of samples in the age group 50 years old was 72.9%. Most of the samples were with the last education of SMA / SMK and worked as self-employed. The average calcium intake was 1081 mg/day. The average number of calories spent during physical activity in one day was 1552 kcal/min. The average of lipid profile was cholesterol 171,90 mg/dl, HDL 37,56 mg / dl, LDL 108,91 mg / dl, and triglyceride was 160,06 mg / dl. The correlation test showed that there was a significant relationship between calcium intake and total cholesterol. The analysis result showed the value (p0,05), while HDL, LDL, and triglyceride were not significant with value analysis (p 0,05). There was no significant relation value of physical activity correlation test with lipid profile level including cholesterol, HDL, LDL, and triglyceride (p0,05). It could be concluded that there was only a significant relationship between calcium intake and cholesterol, whereas there was no significant relationship between calcium intake with HDL, LDL, and triglycerides. And there was a significant relationship between physical activity and lipid profile. Keywords: Coronary Heart Disease, Lipid Profile, Calcium intake, and Physical Activity.